A new perspective on Bruch's membrane and the retinal pigment epithelium. Issue 1 (January 1982) - Goldbaum, M H; Madden, K
Abstract : Trypsin digestion of retinal pigment epithelium is a technique that bares Bruch's membrane, to allow topographical examination by scanning electron microscopy. Twenty-five human eyes were examined. The zonula occludens of the pigment epithelium was clearly seen as a surface feature, but attachment plaques at the sides and base were not visible. The adhesion between the pigment epithelium and the basal lamina was stronger than between the basal lamina and the rest of Bruch's membrane. Surface features of the basal lamina, inner collagenous zone, elastic layer, and outer collagenous zone were seen in a way that previously required an artist's representation constructed from microscopic sections.